Overexpression of miR-135b attenuates pathological cardiac hypertrophy by targeting CACNA1C. (15th October 2018) - Chu, Qun; Li, Anqi; Chen, Xi; Qin, Ying; Sun, Xi; Li, Yanyao; Yue, Er; Wang, Cao; Ding, Xueying; Yan, Yan; Zahra, Syeda Madiha; Wang, Shuo; et al.
Abstract: Background: Cardiac hypertrophy is a serious factor underlying heart failure. Although a large number of pathogenic genes have been identified, the underlying molecular mechanisms of cardiac hypertrophy are still poorly understood. MicroRNAs are a class of small non-coding RNAs which regulate their target genes at the post-transcriptional level. L-type calcium channels play important role in hypertrophic signaling pathways, and CACNA1C is encoded by L-type calcium channels. Here, we hypothesize that the overexpression of miR-135b can attenuate hypertrophy by targeting CACNA1C. Methods: We test the functional involvement of miR-135b in cardiac hypertrophy model. In order to evaluate the effect of miR-135b in cardiac hypertrophy, miR-135b mimic, miR-135b agomir and α-MHC-miR-135b transgenic mice were used for the overexpression of miR-135b. Luciferase reporter assays were used to testify the binding of miR-135b to the CACNA1C 3′UTR. Results: Our results revealed that in a pathological cardiac hypertrophy model, the expression of miR-135b was clearly downregulated. Hypertrophic marker genes were upregulated after the knockdown of miR-135b in vitro, while the overexpression of miR-135b attenuated hypertrophy. These results suggested that miR-135b may weaken hypertrophic signals. We then explored the mechanism of miR-135b in hypertrophy and identified that CACNA1C was a target gene for miR-135b. The overexpression of miR-135b attenuated cardiac hypertrophy by targeting CACNA1C. Conclusions: Our studies revealed that miR-135b is a critical regulator of cardiomyocyte hypertrophy. Our findings may provide a novel strategy for the treatment of cardiac hypertrophy. Highlights: Loss expression of miR-135b was found in pathological cardiac hypertrophy models both in vivo and in vitro . CACNA1C was a direct target gene of miR-135b. The overexpression of miR-135b could attenuate pathological cardiac hypertrophy by targeting CACNA1C.